2013
DOI: 10.1021/jp4042793
|View full text |Cite
|
Sign up to set email alerts
|

Photo- and Radiation-Chemistry of Halide Anions in Ionic Liquids

Abstract: One- and two- photon excitation of halide anions (X(-)) in polar molecular solvents results in electron detachment from the dissociative charge-transfer-to-solvent state; this reaction yields a solvated halide atom and a solvated electron. How do such photoreactions proceed in ionic liquid (IL) solvents? Matrix isolation electron paramagnetic resonance (EPR) spectroscopy has been used to answer this question for photoreactions of bromide in aliphatic (1-butyl-1-methylpyrrolidinium) and aromatic (1-alkyl-3-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…[21][22][23][24] Several research groups have investigated the radiation stability of different hydrophobic ILs using various methodologies. [18,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] An assessment of the radiation effects of ,  and  on imidazolium cation based hydrophilic ILs show less than 1 % degradation of the media even when exposed to a dose of 400 kGy, which suggests very high radiation stability for these ILs. [25] Some studies reported changes in the physical properties such as density, viscosity, conductivity, surface tension and refraction index after -radiolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] Several research groups have investigated the radiation stability of different hydrophobic ILs using various methodologies. [18,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] An assessment of the radiation effects of ,  and  on imidazolium cation based hydrophilic ILs show less than 1 % degradation of the media even when exposed to a dose of 400 kGy, which suggests very high radiation stability for these ILs. [25] Some studies reported changes in the physical properties such as density, viscosity, conductivity, surface tension and refraction index after -radiolysis.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47] Shkrob et al have investigated radical generated species by EPR spectroscopy, showing different degradation pathways for aromatic and aliphatic ILs. [18,[35][36][37][38][39][40][41][42] Degradation pathways have been proposed on the basis of final product identification using spectrometric techniques such as NMR, electrospray ionization mass spectrometry (ESI-MS) and liquid chromatography coupled with ESI-MS. [26,27] The anion effect on the stability of imidazolium based ILs has been reported using spectrometric techniques. [29] All of these studies suggest that many radiolysis products are formed from ILs, but in small quantities, and that the mechanisms are difficult to quantify.…”
Section: Introductionmentioning
confidence: 99%
“…They studied photoreactions, where bromine atoms are being formed after photoexcitation that abstract hydrogen from alkyl chains of the cation. Therefore, no solvated bromine radicals in RTILs could be formed [74] …”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Shkrob and Wishart (Shkrob et al 2013;Wishart and Shkrob 2009) used a combination of computational chemistry methods, low-temperature electron spin resonance and TA spectroscopy to study electron localization in imidazolium-based ILs. They propose that the electron localization on the imidazolium cation produces a gauche dimer radical cation (C 2 +• ) via reaction of the BMIm • radical with a BMIm + cation, and that these species should absorb in the near-IR and the visible to near-UV regions.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Furthermore, they go on to show that the TA kinetics observed at a single wavelength strongly depend upon the scan rate, suggesting possible contributions from stable photo-products. (Brands, Chandrasekhar, and Unterreiner 2007) In earlier work (Shkrob et al 2013) part of our team observed that in dilute solutions of C n MIm + /Brin C n MIm + /NTf 2 -, the released halogen atom very rapidly abstracts H from the aliphatic arms of the IL cations, forming HBr, the dimer radical,…”
Section: Introduction §mentioning
confidence: 95%